مشكلات تعليم الصرف وحلولها للمبتدئين - Faedurrohman Faedurrohman; Agung Muttaqien; Muhammad Afthon Ulin Nuha (Kalimatuna: Journal of Arabic Research, 2023)
This study aims to determine the problems of learning sharf (Arabic morphological) and its solutions for novice learners. The method used in this research is qualitative with the type of library research. The technique used in data collection was to conduct a search of the books and results of sharaf's research that had been published. The data analysis uses interactive data analysis Miles, Huberman and Saldana. The results of this study indicate that learning sharf problems include two aspects, namely material aspects and teaching aspects. The problems of sharf learning from the material aspect are due to the fact that there is no design for presenting sharf material systematically according to the level of student learning. Meanwhile, from the teaching aspect, it is because the method used is more theoretical and weak in its application. Therefore, as a solution to the problem mentioned above, it is necessary to develop a systematic and applicable sharf learning design which contains three elements, namely habituation, memorization and practice.